A hand‐held device with 3‐DOF haptic feedback mechanism for microsurgery. Issue 5 (24th July 2019) - Wang, Zhen; Wang, Shuxin; Zuo, Siyang
Abstract: Background: The hand‐held devices have the advantages of being compact and easily integrated into surgical workflow especially for microsurgery. However, one of the technical challenges of hand‐held device in microsurgery is the lack of force sensing and feedback. Methods: This paper presents a hand‐held haptic device that converts imperceptible forces into human‐perceptible tactile signals. It combines a force sensing tip based on fiber Bragg grating (FBG) sensors that can detect three‐degrees‐of‐freedom (3‐DOF) forces, and a haptic feedback mechanism to indicate the magnitude and direction of the forces. Results: Experimental results demonstrate the ability to measure transverse force at the level of millinewton. User trials have been performed to validate the performance of the haptic feedback. During the phantom experiment, the transverse force was reduced with the feedback mechanism. Conclusions: The proposed device provides important insights into the design of hand‐held device incorporating real‐time force sensing and haptic feedback for microsurgery.